2016
DOI: 10.1088/0953-8984/28/47/475303
|View full text |Cite
|
Sign up to set email alerts
|

Optical and transport properties correlation driven by amorphous/crystalline disorder in InP nanowires

Abstract: Indium phosphide nanowires with a single crystalline zinc-blend core and polycrystalline/amorphous shell were grown from a reliable route without the use of hazardous precursors. The nanowires are composed by a crystalline core covered by a polycrystalline shell, presenting typical lengths larger than 10 μm and diameters of 80-90 nm. Raman spectra taken from as-grown nanowires exhibited asymmetric line shapes with broadening towards higher wave numbers which can be attributed to phonon localization effects. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Semiconductor materials have been widely employed in highefficiency photosensitive systems, mainly as thin films, substrates or nanowires [1]. Most of them are composed of alloys produced by elements of the groups III−V , such as indium phosphide (InP), whose inherent presence of a direct bandgap (1.34 eV at 300 K) in the visible-near-infrared (vis-NIR) range guarantees its sensitivity to electronic excitations in the visible range of solar radiation [2]. Allied to the great values of surface-to-volume ratio at the nanometer scale, these remarkable tools are currently being investigated for employment as a new generation of photo-electronic devices [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Semiconductor materials have been widely employed in highefficiency photosensitive systems, mainly as thin films, substrates or nanowires [1]. Most of them are composed of alloys produced by elements of the groups III−V , such as indium phosphide (InP), whose inherent presence of a direct bandgap (1.34 eV at 300 K) in the visible-near-infrared (vis-NIR) range guarantees its sensitivity to electronic excitations in the visible range of solar radiation [2]. Allied to the great values of surface-to-volume ratio at the nanometer scale, these remarkable tools are currently being investigated for employment as a new generation of photo-electronic devices [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, InP nanowires have been demonstrated to be a class of very promising key materials to be used in photovoltaic systems due to their high photosensitivity [2,5]. Studies on devices built from semiconductor nanowires and ferromagnetic contacts have demonstrated that both spin and charge can be explored in order to get spintronic functionalities [6].…”
Section: Introductionmentioning
confidence: 99%